Baitolo, a double Iberian inscription on a lead anchor stock from the 1st c. BC (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The lead stock in the Guerra collection is the first of its category found with an Iberian inscription: baitolo. The most feasible interpretation is to consider it as a place name, either as the name of the city of baitolo/Baetulo, the modern Badalona, which issued coins with the legend baitolo in the 2nd quarter of the 1st c. BC, or as the name of the nearby river, the modern Besós. Greek and Roman inscriptions on stocks basically contain ship-owner names and deity names. In the latter case, they coincide with the name of the ship, which would also allow a place name to be expected on a stock, as geographical ship names are frequent. The ship that carried this anchor was built in the middle of the 1st c. BC and most probably belonged to a Laietanian ship-owner from the Ibero-Roman city of baitolo/Baetulo.
Keywords: Hispania; Baitolo; Baetulo; Palaeohispanic Epigraphy; Lead anchor stock